Cooled Radiofrequency Ablation in Shoulder Pain: A Cohort study - Nava Obregón, Teresa Adriana; Palacios Ríos, Dionicio; López Ríos, Francisco; Castillo Guzmán, Sandra; Torres Pérez, Juan Francisco; Simental Mendía, Mario Alberto; Acosta Olivo, Carlos Alberto (2025)
Objective: This study aims to evaluate the pain and clinical evolution of patients with shoulder pain with cooled radiofrequency ablation (CRFA). Methodology: A cohort prospective study of patients with shoulder pain for >3 months. All patients included were treated with CRFA in the sensitive innervation around the shoulder (lateral pectoral, suprascapular nerve, axillary nerve), and were followed for 24 weeks. Pain was evaluated with the visual analog scale, while clinical evolution was evaluated with several scales of shoulder function. Results: Fifteen patients were included. All patients improved significantly the pain during the time of the study. The clinical function of the shoulder shows a significant improvement during the 24 weeks of follow up. Conclusions: CRFA is a medical procedure that helps to improve pain and function related to shoulder pain independently of the primary pathology in the shoulder